A Phase 2 Proof‐of‐Concept, Randomized, Placebo‐Controlled Trial of CX‐8998 in Essential Tremor. Issue 8 (25th March 2021) - Papapetropoulos, Spyros; Lee, Margaret S.; Versavel, Stacey; Newbold, Evan; Jinnah, Hyder A.; Pahwa, Rajesh; Lyons, Kelly E.; Elble, Rodger; Ondo, William; Zesiewicz, Theresa; Hedera, Peter; Handforth, Adrian; et al.
Abstract: Background: Available essential tremor (ET) therapies have limitations. Objectives: The objective of this study was to evaluate CX‐8998, a selective T‐type calcium channel modulator, in essential tremor. Methods: Patients 18–75 years old with moderate to severe essential tremor were randomized 1:1 to receive CX‐8998 (titrated to 10 mg twice daily) or placebo. The primary end point was change from baseline to day 28 in The Essential Tremor Rating Assessment Scale performance subscale scored by independent blinded video raters. Secondary outcomes included in‐person blinded investigator rating of The Essential Tremor Rating Assessment Scale performance subscale, The Essential Tremor Rating Assessment Scale activities of daily living subscale, and Kinesia ONE accelerometry. Results: The video‐rated The Essential Tremor Rating Assessment Scale performance subscale was not different for CX‐8998 (n = 39) versus placebo (n = 44; P  = 0.696). CX‐8998 improved investigator‐rated The Essential Tremor Rating Assessment Scale performance subscale ( P  = 0.017) and The Essential Tremor Rating Assessment Scale activities of daily living ( P  = 0.049) but not Kinesia ONE ( P  = 0.421). Adverse events with CX‐8998 included dizziness (21%), headache (8%), euphoric mood (6%), and insomnia (6%). Conclusions: The primary efficacy end point was not met; however, CX‐8998 improved some assessments of essential tremor, supporting further clinical investigation. © 2021 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society. This article has been contributed to by US Government employees and their work is in the public domain in the USA.